Pengaruh Budaya Organisasi terhadap Kinerja Panitia Pemilihan Kecamatan (PPK) Pemilu 2024 Se-kabupaten Batang Hari - Darma, Budi; Wulansari, Kasiyati Yunita (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The title of this research is "The Influence of Organizational Culture on the Performance of the Panitia Pemilihan Kecamatan (PPK) of the 2024 Elections in Batang Hari District." This study aims to determine the influence of organizational culture on the performance of the Panitia Pemilihan Kecamatan (PPK) of the 2024 Elections in Batang Hari District. To achieve this research objective, simple linear regression analysis is used as the analytical tool. This is done because this research only applies one independent variable, namely organizational culture. Additionally, t-test and coefficient of determination are also utilized in this study. In the t-test analysis, the organizational culture variable influences the performance of the Panitia Pemilihan Kecamatan (PPK) of the 2024 Elections in Batang Hari District individually (partially). In the Coefficient of Determination test, organizational culture influences the performance of the District Election Committee (PPK) of the 2024 Elections in Batang Hari District by 76.96%. Meanwhile, 23.1% of the influence on the performance of the Panitia Pemilihan Kecamatan (PPK) of the 2024 Elections in Batang Hari District is affected by other variables not examined in this study